Interplay between structural design, morphology, and magnetism in Fe60Al35Zn5 nanostructures - Hafs, Toufik; Berdjane, Djamel; Hafs, Ali; Ayaz, Ramazan (INDIAN ASSOC CULTIVATION SCIENCE, 2026)
This study investigates the effect of milling time on phase evolution, microstructure, and magnetic properties of a nanostructured Fe60Al35Zn5 (wt.%) alloy synthesized by mechanical alloying. High-energy ball milling was applied for 0-36 h. X-ray diffraction analysis (Rietveld refinement via MAUD) revealed the formation of an Fe(Al,Zn) solid solution after 12h, with the lattice parameter increasing to similar to 0.287 nm after 36h. Crystallite size decreased to similar to 16 nm, while microstrain reached similar to 1.12%. SEM observations showed initial heterogeneous particle shapes and sizes, reflecting concurrent fragmentation and agglomeration. With longer milling, particle distribution became more uniform, indicating a balance between fracture and welding, and morphological stabilization after 36h. EDX elemental mapping confirmed homogeneous distribution of Fe, Al, and Zn, validating alloy formation. Magnetic characterization by VSM provided insights into the evolution of saturation magnetization, coercivity, and remanence with milling duration, establishing a clear link between nanostructure and magnetic behavior.
Keywords: Powder; Microstructure; Morphology; X-Ray diffraction (XRD); Magnetic properties; IRON ALUMINIDES; POWDERS; NI; NANOMATERIALS; METALS; Physics